Superconducting and low-temperature particle detectors : proceedings of Symposium C on Superconducting and Low-Temperature Particle Detectors of the 1988 E-MRS Fall Conference, Strasbourg, France, 8-10 November 1988 - Waysand, G.; Chardin, G. (European Materials Research Society symposia proceedings, 1989)
As demonstrated by the contributions in this volume, the domain of superconducting and low-temperature devices is in a rapidly expanding phase. Interactions between materials sciences, low-temperature physics, astrophysics, nuclear and particle physics have provided the incentive for new experiments, which could ultimately record such rare interactions as double beta decay, neutrino scattering, or collisions of the elusive dark matter halo particles. The theoretical and experimental improvements achieved during the last year have been impressive. Detection of 60 keV resolution with a non-zero spin material as a target seems therefore realizable in the near future. Similarly, impressive achievements on ballistic phonons detection and superheated superconducting detectors have been presented, together with reliable techniques for developing ultra low noise electronics required by these ambitious experiments. Apart from the contributions presented during the symposium, the two original papers by Niinikoski proposing the use of bolometers as particle detectors have been included in this volume. These papers, despite their current interest, have never been published before. The comprehensive style of the papers will appeal to specialists and non-specialists alike, in particular solid-state physicists will find the volume of considerable interest, as the field of materials research continues to benefit from the type of work presented here.